A SEMIOTIC ANALYSIS ON THE LOGOS OF THREE CAFES IN MALANG - FIRMANSYAH, AGUNG (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Semiotics, Logo, Sign, Connotation, Icon, Index, Symbol.Cafe is very popular in Malang and it usually has a logo to show the characteristics of the cafe and all identities or all aspects of the cafe. In this research, the researcher chooses three logos of cafes in Malang. Then, to get the meaning of the logos, the researcher analyzes them by using semiotic study. This research has three problems of the study to be answered: (1) What typology of signs are found on the logos of three cafes in Malang? (2) What are the connotations of the logos of three cafes in Malang?, and (3) What are the relationships between the sign connotation of the logos of cafes and the history, concept and goals of the cafes?Descriptive qualitative research with content or document analysis is applied in this research. The data analysis is conducted by applying Pierce’s theory (1931 in Chandler 2007) that is typology of sign. In order to interpret the meaning of the signs found, connotation theory offered by Chandler (2007) and Fiske (2012) are also used. Purposive sampling is used in this research to select the objects. In this research, the researcher selected Uno cafe, Mochi Maco cafe, and Omah Coffee Cafe.The result of this research discovers that the icon, index, and symbol are found in the logos. The iconic signs are mostly applied and the symbolic signs are used more than the indexical one. The meaning of signs combination found in the logos is interpreted through connotation theory. In accordance with the analysis, the three cafes represent their characteristics through their logos and the three logos of cafes show relationships between the signs connotation and the history, concept, and goals of the cafes. Moreover, the three logos represent characteristics and relation between the sign connotation of the logo and the history, concept, and goal of the café through their symbolic signs in their names.The researcher finally suggests the next researchers analyze other objects as the data source conducting a research related to semiotics study such as posters, novel covers, posters and different logos of cafes in areas other than Malang.